DETERMINAN MANAJEMEN LABA PADA PERUSAHAAN YANG MELAKUKAN PENAWARAN SAHAM PERDANA - Ike Anis Marsela; Tatang Ary Gumanti; Marmono Singgih (Jurnal Akuntansi Bisnis, 2016)
This article aimstoanalyze the effect ofoperatingcash flows, size of thecompany, earnings changes, andfinancial leverage onearnings managementchangesin the basic industry and chemicalsub-sectormaking initial public offering in theIndonesia Stock Exchange. The samples were selected using purposive sampling method in which as many as 35 out of 60 companies in the period 1989-2013. The data used are secondary data from a basic industry and chemical sub sector. The companys prospectus is obtained from database of the Economic Faculty, University of Jember, Indonesian Capital Market Directory (ICMD), and other sources. This usesmultiple linearregressionanalysis to test the hypotheses. The dependent variable is earnings management measured using the ratio of DCA models of Friedlan. Independent variables consisted of operating cash flow, size of the company, earnings changes, and financial leverage. Results showedthatoperatingcash flows negatively andsignificanty affectearnings managementchanges, earningschanges have positive andsignificant effect onearnings managementchanges, size of the company andfinancial leveragedoes not havesignificant effecton earnings management changes.